2020
DOI: 10.1101/2020.04.11.037473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiscale 3-dimensional pathology findings of COVID-19 diseased lung using high-resolution cleared tissue microscopy

Abstract: The study of pulmonary samples from individuals who have died as a direct result of COVID-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
1
28
0
3
Order By: Relevance
“…Так, в исследовании D.Wichmann et al [19] отмечается высокая частота (58 %) глубоких венозных тромбозов у 12 умерших, в работе C.Edler et al -у 40 % из 80 умерших [20]. Во многих работах подтверждена высокая частота обнаружения тромбов и микротромбов в легких [21,22]. В данном исследовании частота выявления тромбов в ветвях легочной артерии, вен и микрососудах составила 42,78, 25,20 и 9,76 % соответственно.…”
Section: результатыunclassified
See 2 more Smart Citations
“…Так, в исследовании D.Wichmann et al [19] отмечается высокая частота (58 %) глубоких венозных тромбозов у 12 умерших, в работе C.Edler et al -у 40 % из 80 умерших [20]. Во многих работах подтверждена высокая частота обнаружения тромбов и микротромбов в легких [21,22]. В данном исследовании частота выявления тромбов в ветвях легочной артерии, вен и микрососудах составила 42,78, 25,20 и 9,76 % соответственно.…”
Section: результатыunclassified
“…Коагулопатия является частым проявлением при тяжелом течении COVID-19. Так, в исследовании [22] (n = 191) признаки нарушения свертывания отмечались у 50 % умерших от COVID-19 по сравнению с 7 % случаев наличия таковых у выживших. Высокая концентрация D-димера (> 1 000 мкг / мл) является прогностически неблагоприятным фактором, ассоциированным с высоким риском смерти.…”
Section: результатыunclassified
See 1 more Smart Citation
“…For the first study, Eckermann et al [55] developed and demonstrated the utility of a phase contrast x-ray tomography concept to investigate unstained lung tissue. The second study describes the use of fluorescent H&E-analog stains (TO-PRO-3 for nuclear contrast and Eosin-Y for cytoplasmic/stromal contrast) to achieve “3D pseudo-histological imaging” [56]. Consequently, our study constitutes the first report of direct 3D visualization of SARS-CoV-2 infection via LSFM.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the opportunities and advantages of TOC for virus research have been demonstrated in several studies [4954]. While two approaches to 3D imaging of SARS-CoV-2-infected lung tissue have been described recently [55,56], neither of them is capable of direct visualization of SARS-CoV-2 infection via virus-specific antigen staining.…”
Section: Introductionmentioning
confidence: 99%